Changes of laminar angle in cervical double-door laminoplasty -comparison of conventional method and suture anchor method using computed tomography images- a pilot study - Shingo Morishita; Takashi Hirai; Kentaro Yamada; Masato Yuasa; Yu Matsukura; Satoru Egawa; Hiroaki Onuma; Jun Hashimoto; Toshitaka Yoshii (BMC Musculoskeletal Disorders)
Abstract Background Laminar closure rarely occurs in conventional laminoplasty (LAMP). Thus, various techniques have been developed to maintain the laminar opening using the suture anchor. However, no studies have examinced the two surgical methods using computed tomography. This study aimed to compare LAMP using the suture anchor and conventional LAMP in terms of laminar opening maintenance. Methods This study included patients who underwent double-door LAMP from C3 to C7 according to the Kirita-Miyazaki method (conventional group, where the lamina was sutured to the deep fascia) or using suture anchors (anchor group). The laminar angles from C3 to C6 were measured using cervical spine computed tomography intraoperatively, 1 week postoperatively, and 1 year postoperatively, respectively, in the conventional and anchor groups. We measured the C2–C7 lordotic angle, T1 or C7 slope, and cervical sagittal vertical axis by X-ray and investigated the 1-year postoperative recovery rate with Japanese Orthopaedic Association scores. Results The anchor group consisted of 11 patients and the conventional group consisted of 9 patients. The laminar angles at C4, C5, and C6 were significantly greater in the anchor group both intraoperatively, 1 week postoperatively, and 1 year postoperatively. C3 had a slightly larger laminar angle in the anchor group but was not significant. The C3 laminar angle decreased over time in both groups. The laminar angle for C4, C5, and C6 in the anchor group was maintained intraoperatively to 1 year postoperatively. The laminar angle did not change beyond 1 week postoperatively in the conventional group. Conclusions The laminar angle in the anchor group was maintained intraoperatively to 1 year postoperatively, while the conventional group tended to close immediately postoperatively. The suture anchor technique may maintain laminar opening more rigidly than the conventional suture method.